2015
DOI: 10.1007/s11664-015-4092-y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Bulk Cu6Sn5 Nucleation in Sn0.7Cu/Cu Joints with Al Micro-alloying

Abstract: We show that dilute Al additions can control the size of primary Cu6Sn5 rods in Sn-0.7Cu/Cu ball grid array (BGA) joints. In Sn-0.7Cu-0.05Al/Cu joints, the number of primary Cu6Sn5 per mm 2 is ~7 times higher and the mean three dimensional (3D) length of rods is ~4 times smaller than in Al-free Sn-0.7Cu/Cu joints, while the area fraction of primary Cu6Sn5 is similar. It is shown that epitaxial nucleation of primary Cu6Sn5 occurs on δ-Cu33Al17 or γ1-Cu9Al4 particles, which are stable in the Sn-0.7Cu-0.05Al melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Primary Cu6Sn5 has been reported to grow with various morphologies such as needles [10][11][12], hollow rods [11,13], X-shapes [9,14,15], Y-shapes [8,9], H-and M-shapes [16,17] and as dendrites [6,18]. Since many of these studies have been based on arbitrary 2D cross sections, it is not clear how many of these morphologies are separate growth forms in 3D.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary Cu6Sn5 has been reported to grow with various morphologies such as needles [10][11][12], hollow rods [11,13], X-shapes [9,14,15], Y-shapes [8,9], H-and M-shapes [16,17] and as dendrites [6,18]. Since many of these studies have been based on arbitrary 2D cross sections, it is not clear how many of these morphologies are separate growth forms in 3D.…”
Section: Introductionmentioning
confidence: 99%
“…The growth direction of the rod-like Cu6Sn5 is reported to be [0001] and the growth facets are usually {11 ̅ 00}-type Cu6Sn5 planes [15,16,19,20]. The crystallographic directions and facets of the other growth forms are not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[52] indicate that large intermetallics, which includes the primary and interfacial intermetallic compound layer, could promote crack initiation in solder joints. Xian et al [54] report that primary Cu6Sn5 formation in the bulk solder is shown to be affected by the increasing Cu content of the liquid due to the Cu dissolution, the change in phase equilibria and the degree of undercooling for β-Sn.…”
Section: Fabrication Methods Of Reinforced Soldersmentioning
confidence: 99%
“…by crystal growth prior to Sn nucleation) such as the large Ag3Sn plates and Cu6Sn5 rods in BGA joints [53][54][55]. Under BGA soldering conditions the IMCs typically grow as faceted crystals [54,56].…”
Section: Cte Mismatch At Sn-imc Interfacesmentioning
confidence: 99%